Advanced prostate cancer diagnosed by bone metastasis biopsy immediately after initial negative prostate biopsy: a case report and literature review - Liu, Mingwen; Xie, Zhifei; Tang, Wen; Liang, Guobiao; Zhao, Zeju; Wu, Tao (Frontiers in Oncology, 2024)
Prostate cancer (PCa) is a prevalent male malignancy that originates in the epithelial cells of the prostate. In terms of incidence and mortality of malignant tumors in men, PCa ranks second and fifth globally and first and third among men in Europe and the United States, respectively. These figures have gradually increased in recent years. The primary modalities used to diagnose PCa include prostate-specific antigen (PSA), multiparametric magnetic resonance imaging (mpMRI), and prostate puncture biopsy. Among these techniques, prostate puncture biopsy is considered the gold standard for the diagnosis of PCa; however, this method carries the potential for missed diagnoses. The preoperative evaluation of the patient in this study suggested advanced PCa. However, the initial prostate puncture biopsy was inconsistent with the preoperative diagnosis, and instead of waiting for a repeat puncture of the prostate primary, we performed a biopsy of the rib metastasis, which was later diagnosed as advanced PCa.